Assessment of organizations as catalysts for community development an application of the multi nominal logit model - Gordoncillo, Prudenciano U. (The Journal of Public Affairs and Development, 2012)
Agrarian Reform Communities or ARCs are clusters of land reformed barangays primarily composed and managed by Agrarian Reform Beneficiaries who are willing to be organized and undertake the integrated development of an area and/or their organizations/cooperatives. Organizations serve as channel for support services such as credit, marketing support, and training programs. To measure the level of development of ARCs, the Department of Agrarian Reform developed a quantitative assessment tool known as the ARC Level of Development Assessment (ALDA). This paper used the data drawn from a survey of cooperatives in the ARCs in selected provinces of MIMAROPA, Bicol Region, Western Visayas, Eastern Visayas, and Western Mindanao. The key variables analyzed in the model are the ALDA rating, knowledge and practice scores, which served as the proxy variable for the functionality of the organizations, the proportion of inactive members in the organization, and the total number of members. The estimates of the multi nominal logit model showed that the level of functionality of the organizations significantly influences the level of community development. Specifically, the better is the functionality of the organization, the higher is the likelihood that the ARC will have a higher ALDA rating.